Comparison of the Microwave and Conventional Sintering of Alumina: Effect of MgO Doping and Particle Size. Issue 6 (2nd May 2013) - Zuo, Fei; Carry, Claude; Saunier, Sébastien; Marinel, Sylvain; Goeuriot, Dominique; Bordia, R.
<x xml:space="preserve">Abstract</x> The effects of MgO doping and specific surface area of powder on microwave sintering behavior of α‐Al2O3 were investigated. A comparative study was simultaneously achieved in conventional and microwave heating with an identical thermal process. The experimental results show that both MgO and particle size have significant influence on microwave enhancement in the densification of the alumina samples. It is found that an amount of MgO surrounding the solubility limit in Al2O3 or leading to second phase precipitation of MgAl2O4 spinel induces more significant microwave enhancement. A significant microwave gain in densification is also observed while powder has a high specific surface area. These results indicate that the enhancements during microwave sintering processes are associated with the formation of lattice defect and with the increase in concentration of grain‐boundary region.